2015
DOI: 10.7554/elife.06744
|View full text |Cite
|
Sign up to set email alerts
|

MutS/MutL crystal structure reveals that the MutS sliding clamp loads MutL onto DNA

Abstract: To avoid mutations in the genome, DNA replication is generally followed by DNA mismatch repair (MMR). MMR starts when a MutS homolog recognizes a mismatch and undergoes an ATP-dependent transformation to an elusive sliding clamp state. How this transient state promotes MutL homolog recruitment and activation of repair is unclear. Here we present a crystal structure of the MutS/MutL complex using a site-specifically crosslinked complex and examine how large conformational changes lead to activation of MutL. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
150
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(171 citation statements)
references
References 72 publications
17
150
0
Order By: Relevance
“…A recently published study demonstrated that addition of E. coli MutL greatly reduces the rate at which MutS slides off mismatched DNA, consistent with our findings (41).…”
Section: Note Added In Proofsupporting
confidence: 93%
“…A recently published study demonstrated that addition of E. coli MutL greatly reduces the rate at which MutS slides off mismatched DNA, consistent with our findings (41).…”
Section: Note Added In Proofsupporting
confidence: 93%
“…These functional data are in line with crystal structures of MutS proteins showing that the ATPase sites are located at the dimer interface and have a composite nature, with each subunit contributing residues to the site on the other subunit (Fig. 1) [50,51], and that ATP binding tightens the interface [26,43,52,53]. Bulk kinetic measurements of fluorophore-labeled Taq MutS domains I under the same reaction conditions reveal robust allosteric signaling between the ATPase and DNA binding sites despite their distant locations (~70 Å apart), with the protein flipping rapidly between two distinct conformations, one upon ATP binding to both subunits (10 6 M −1 s −1 at 40 °C) and the other upon ATP hydrolysis at the tight site (10 s −1 at 40 °C; Fig.…”
Section: Muts Actions In Mmrsupporting
confidence: 80%
“…3, 4c) [23,58]. In addition to domains I moving away from the mismatch [58], new structural data indicate that domains IV cross each other (keeping the clamp closed) and the connector domains II move outward [53]; hence, ATP-bound MutS can slide on DNA [41,59] without rotating along the helical contour, as confirmed recently by sm-tracking experiments with Taq and yeast MutS proteins [18-21,60]. It is surprising that after the effort of finding and marking a rare mismatch on DNA (akin to finding a needle in a haystack), MutS adopts a mobile state that can diffuse freely away from the MMR target site.…”
Section: Muts Actions In Mmrmentioning
confidence: 99%
“…One of the key postulated benefits of sexual recombination is the reduction of Muller's ratchet. To determine whether the recombination-proficient strain can effectively achieve this during an ALE experiment, we generated a mutator version of our strain by deleting mutS, the mismatch recognition component of the mismatch repair system (48,49), and carried out an ALE experiment in rich medium (LB) for ϳ850 generations. The mutation rate of the ⌬mutS strain was increased by ϳ200-to 300-fold in both the genderless mutator and the asexual 2xoriT mutator strains over that of the nonmutator counterparts HFR-2xoriT-SFX and BW25113-2xoriT, respectively.…”
Section: Resultsmentioning
confidence: 99%